Aligning English Language Testing With Curriculum - Marcela Palacio; Sandra Gaviria; James Dean Brown (Universidad Nacional de Colombia, 2016)
Frustrations with traditional testing led a group of teachers at the English for adults program at Universidad EAFIT (Colombia) to design tests aligned with the institutional teaching philosophy and classroom practices. This article reports on a study of an item-by-item evaluation of a series of English exams for validity and reliability in an effort to guarantee the quality of the process of test design. The study included descriptive statistics, item analysis, correlational analyses, reliability estimates, and validity analyses. The results show that the new tests are an excellent addition to the program and an improvement over traditional tests. Implications are discussed and recommendations given for the development of any institutional testing program.